Branding Leadership: Mastering Competencies from Outside In - Daash, Annjaan; Pal, Prabir; S. , Pragadeeswaran (International Journal of Psychosocial Rehabilitation, 2020)
Leadership and leaders are both sides of a coin, as both matter. The cynosure is the leader and embraces the qualities of the individual and how they lead and involve others. A leader focuses on competencies like knowledge, skills, and abilities and shows a clear path to the individuals so that they are adept in potentiality and are able to manage others. Emphasizing leadership highlights the caliber of leaders within an organization, not merely an individual leader but the entire system and the processes that generate these leaders. Outstanding leaders might appear and exit, but the tide of leadership remains forever. Genuine leadership doesn’t deal with a single person, but it also takes into account the entire process. We can appreciate and gain knowledge from any person who is an impressive or excellent leader. The final outcome of an organization’s leadership robustness is obtained by building a leadership pipeline that entrusts stakeholders’ confidence in achieving future results. Leadership focuses on an individual, whereas building leadership emphasizes the organization that generates leaders. Leadership brand is the identity of the leaders throughout the organization that bridges customer expectations and employee and organizational behavior. (Ulrich et al., 2007). Leadership necessitates the opinion about the X factor, or the systems and processes that raise the next generation of leaders who will respond to the future customer and investor assurance. Branding leadership also helps in building the next generation of leaders. Firms with a leadership brand have an eternal and durable reputation. When the organization’s brand intertwines with its leadership brand, the former sustains and outlives any single individual leader.